An Examination of the Relationship Between Media Exposure and Fear of Victimization: Implications of the Superpredator Narrative on Juvenile Justice Policies. (29th December 2020) - Allen, Terrence T.; Whitt, Ahmed
Abstract: The media allow crime to infiltrate the public's consciousness in every conceivable way, thereby playing a major role in shaping the public's opinion and attitude toward crime and crime issues (Barak, 1995; Fields & Jerin, 1996; Kappeler & Potter, 2005). Reporters constantly talk about crime, and crime related stories dominate the headlines of local and national newspaper outlets (Dowler, 2003; Pizarro et al, 2007). Some of the most highly rated television programs are based on crime plots and people across social, political, and racial demographics are constantly engaged in crime dialogue generated from local or national news stories. When the focus of these mediums is on youth they become even more profound and contentious. The images portrayed conjure up stereotypes that lead to fear and inflammatory remarks that become entrenched into the national lexicon. The current study uses data from the National Opinion Survey of Crime and Justice to test the relationship between crime‐related media viewership and fear of victimization within a nationally representative adult sample. Approximately 42.67% of respondents reported regularly watching crime shows and about the same proportion (42.83%) believed their local media paid too much attention to violent crime. In addition to regular crime‐show viewership, confidence in the police, gender, and recent contact with the police were associated with fear of victimization. This article adds to an existing body of research through a largely unexplored area in the administration of justice. It does so within the context of the U.S. juvenile justice system.